The Application of Epstein’s Model in the Implementation of Career Transition Programme for Students with Learning Disabilities - Nurulhuda Mohamed Nor; Mohd Hanafi Mohd Yasin (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2018)
The career transition programme is a programme implemented to prepare students with special needs (SSN) to face future working environment. Parents are among the factors contributing to the successful completion of SSN’s career transition programme. This survey was conducted to identify the level of involvement of SSN parents in the implementation of career transition programmes in schools. The instrument used in this study was a questionnaire consists of 48 items with five points Likert scale. This questionnaire was developed based on six elements of Epstein’s Parental Involvement Model: i) parenting, ii) communication, iii) decision making, iv) learning at home, v) collaboration with the community and vi) voluntary assistance. This study involved 30 respondents comprising parents of SSN who had undergone a career transition programme at Special Education Integrated Program (PPKI) at four secondary schools in Seremban, Negeri Sembilan. The data were analysed descriptively using SPSS software. The findings show that parents’ involvement is high in terms of communication and voluntary assistance while their involvement in parenting, decision-making, home-based learning, and collaboration with the community is at moderate level. Parents’ education level was found to have no significant relationship with the level of parental involvement except for communication and voluntary aspects. The findings of this study can give some insights to policy makers to increase parents’ level of involvement in the context of planning and the implementation of programmes to support SSN’s readiness for the career realm. Parents are encouraged to improve their advocacy skills and awareness on the importance of their roles in the career transition.